Compound Heterozygous Hemoglobin SD Disease Presenting as Sickle Cell Crisis in Pregnancy - Rakhi; Minakshi Rohilla; Pankaj Malhotra; Reena Das; Vanita Jain; GRV Prasad; Jasvinder Kalra (Journal of Women's Reproductive Health, 2016)
A case report of compound heterozygous hemoglobin SD disease presenting as sickle crisis during pregnancy. The discussion covers transfusion, pain control, and peripartum care.
Keywords: Compound Heterozygous